A Novel UPLC Method for the Estimation of Antidiabetic Drugs in Bulk and its Tablet dosage form - Kasimedu, Saravanakumar (Asian Journal of Pharmaceutics (AJP), 2024)
A highly sensitive, precise, and accurate ultra-performance liquid chromatography method was developed and validated for the determination of ertugliflozin and sitagliptin in the combined formulation. Chromatographic separation was carried out on the DIKMA Endeversil C18 column (2.1 mm × 50 mm, 1.7 μm) using the mobile phase of KH2PO4:methanol 45:55 v/v. The common wavelength of absorption of ertugliflozin and sitagliptin was found to be 225 nm. The flow rate was maintained at 0.3 mL/min, with 2 µL injection volume. The retention time of ertugliflozin and sitagliptin was found to be 0.41 min and 0.535 min. % relative standard deviation of the ertugliflozin and sitagliptin was found to be 0.681 and 0.218, respectively. %recovery was obtained as 100.146% and 100.27% for ertugliflozin and sitagliptin, respectively. Limit of detection (LOD), limit of quantification (LOQ) values obtained from regression equations of ertugliflozin and sitagliptin were 2.91, 2.96, and 10.04, 10.09, respectively. Regression equation of ertugliflozin is y = 1329.8 × −228.7 (0.9997) and y = 1294.4.× –40.1 of sitagliptin (0.9998). The proposed method was validated in terms of linearity, precision, accuracy, specificity, LOD, LOQ, and robustness. The method was successfully applied to the estimation of ertugliflozin and sitagliptin tablet dosage forms.